Evaluation of the health information reliability in spanish about Covid-19 on Google - Mujica-Rodríguez, Iván E. (2021)
Background: The COVID-19 pandemic has generated an increase in information about this disease, so it is essential to guarantee the credibility and reliability of the web pages that provide this information. Objective: To evaluate the reliability of health information in Spanish on COVID-19 in Google, considering the criteria of the HONcode tool. Material and methods: Observational cross-sectional study. Google web pages were analyzed on December 2020 from Lima-Peru, using 4 terms. The reliability of the health information on the web pages was evaluated using HONcode tool (version 3.1.3). They were classified according to the source of information and its origin. Statistical analysis was performed for a significance level of p <0.05. Results: 200 web pages in Spanish were evaluated, 16.5% had a HONcode certificate, the majority was from the WHO (33.3%), the main source of information was “academic-professional” (30.0%). In addition, 33.0% of the web pages were Peruvian from the governmental type (42.4%), but none had a HONcode certificate. Conclusions: Only one in six web pages provided reliable health information on COVID-19. In addition, the presence of the WHO web pages in providing health information on COVID-19 on Google is distinguished. Although this study highlights the web pages of international organizations, it is necessary to strengthen communication from the Peruvian government web pages.